Using Chain Story Technique To Develop Speaking Skill Of Grade VIII Students Of SMP Negeri 1 Banawa Tengah - Alkhaf Shaban; Konder Manurung; Zarkiani Hasyim (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The purpose of this research was to determine the effectiveness of the chain story technique in teaching English speaking to grade VIII students of SMP Negeri 1 Banawa Tengah. The study involved two classes, namely class VIII B with 27 students as the experimental group and class VIII A with 28 students as the control group. Data were collected through speaking tests, consisting of pre-test and post-test, and analyzed using simple statistical methods. The findings revealed a significant improvement in the students’ speaking skills, as indicated by the t-count value (8.35) being higher than the t-table value (1.67) at the 0.05 level of significance. Therefore, the research concluded that the chain story technique is effective in teaching English speaking and provides a significant positive impact on students’ speaking skill development.